Inscripción del matrimonio canónico celebrado en españa entre un español y una lituana residentes en el extranjero. Reflexiones sobre la resolución (16ª) de la dgrn de 14 de noviembre de 2019 - Gluhaia, Diana (Univ Carlos III Madrid, 2022)
La Resolución de la DGRN de 14 de noviembre se enfrenta con la cuestión del acceso al Registro Civil español del matrimonio canónico celebrado en España entre un español y una lituana, ambos con domicilio en Londres. La DGRN acepta la inscripción en el Registro civil amparándose fundamentalmente en el Acuerdo entre el Estado español y la Santa Sede sobre asuntos jurídicos.
Registration of the canonical marriage celebrated in spain between a spanish national and a lithuanian woman residing abroad. Reflections on the resolution (16th) of the directorate general of registries and notaries of 14 november 2019
The Resolution of the DGRN of 14 November deals with the question of access to the Spanish Civil Register of the canonical marriage celebrated in Spain between a Spaniard and a Lithua-nian, both domiciled in London. The DGRN accepts the registration in the Civil Register based on the Agreement between the Spanish State and the Holy See on legal matters.
Keywords: matrimonio canónico; certificación eclesiástica; matrimonio celebrado en España entre español y extranjera; Registro Civil español; canonical marriage; ecclesiastical certification; wedding celebrated in Spain between Spaniard and foreigner; Spanish Civil Registry; Scopus